Examination of fetal well‐being evaluation metrics for fetal growth restriction as seen from Japan Obstetric Compensation Cause Analysis Report data. Issue 1 (18th October 2021) - Sugihara, Mika; Unno, Nobuya; Suzuki, Hideaki; Sekizawa, Akihiko; Tanaka, Hiroaki; Fujimori, Keiya; Ikeda, Tomoaki; Shimoya, Koichiro; ,
Abstract: Advances in perinatal care have improved the prognoses of both mothers and neonates; however, cerebral palsy continues to occur. In this study, we examined methods for the intragestational evaluation of the health of infants who later developed cerebral palsy. A retrospective review was conducted on light‐for‐dates cases among the 2113 cause analysis reports issued by the Japan Obstetric Compensation System between January 2009 and September 2018. In our examination, we determined that non‐stress tests and ultrasonic Doppler tests were used to evaluate fetal well‐being. Moreover, we observed cases in which additional testing was not performed even when fetal growth restriction (FGR) was identified. Appropriate management of FGR may help reduce the incidence of cerebral palsy.